BLIMBINGSARI: MODAL SOSIAL DAN PERAN PEMDA DALAM PEMBANGUNAN EKONOMI DI KABUPATEN JEMBRANA, BALI - Junaedi, I Wayan Ruspendi (Jurnal Ekonomi dan Pariwisata, 2017)
ABSTRACT Poverty is the biggest problem in the world and also as an enemy for all nations and we have commitment in order to reduce the poverty . In order to reducing the poverty in the country especially in Blimbingsari, the Local Government needs to develop the economy of their own region so that the regions (society/people) have their own welfare. In this paper the researcher, will explain about the role of the Local Government in kabupaten Jembrana, west Bali, Propince of Bali in order to developed the economy especially in Blimbingsari population, Melaya, Jembrana until they create an new entrepreneurs. From that problem and statement above, the researcher make the main research question is that â€œhow the Social Capital of the society and the local government role in order to develop the society economy in Blimbingsariâ€. From that main research question, the researchr make a research problem in three research question i.e.: (1). What kind of role that the local government do for developing the economic in Blimbingsari? (2). What kind of the social capital that the society do for developing the economic in Blimbingsari? (3). What kind of national program for developing the economic in Jembrana, especially in Blimbingsari? Keyword: Development, Poverty, Role, Local Government, and Social Capital. ABSTRAK Kemiskinan adalah masalah terbesar di dunia dan juga sebagai musuh bagi semua bangsa dan kami memiliki komitmen untuk mengurangi kemiskinan. Dalam rangka untuk mengurangi kemiskinan di negara terutama di Blimbingsari, Pemerintah Daerah perlu mengembangkan perekonomian daerah mereka sendiri sehingga daerah (masyarakat / orang) memiliki kesejahteraan mereka sendiri. Dalam makalah ini peneliti, akan menjelaskan tentang peran Pemerintah Daerah di kabupaten Jembrana, Bali barat, Propince Bali dalam rangka mengembangkan ekonomi terutama di populasi Blimbingsari, Melaya, Jembrana sampai mereka membuat pengusaha baru. Dari masalah itu dan pernyataan di atas, peneliti membuat pertanyaan penelitian utama adalah bahwa "bagaimana Modal Sosial masyarakat dan peran pemerintah daerah dalam rangka mengembangkan perekonomian masyarakat di Blimbingsari". Dari pertanyaan penelitian utama, researchr membuat masalah penelitian di tiga pertanyaan penelitian mis .: (1). Apa peran bahwa pemerintah daerah lakukan untuk mengembangkan ekonomi di Blimbingsari? (2). Apa jenis modal sosial yang masyarakat lakukan untuk mengembangkan ekonomi di Blimbingsari? (3). Apa jenis program nasional untuk mengembangkan ekonomi di Jembrana, terutama di Blimbingsari? Kata kunci: Pengembangan, Kemiskinan, Peran, Pemerintah Daerah, dan Modal Sosial.